2021
DOI: 10.1108/gkmc-04-2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

Twitter sentiment analysis of app based online food delivery companies

Abstract: Purpose There is a strong need for companies to monitor customer-generated content of social media, not only about themselves but also about competitors, to deal with competition and to assess competitive environment of the business. The purpose of this paper is to help companies with social media competitive analysis and transformation of social media data into knowledge creation for decision-makers, specifically for app-based food delivery companies. Design/methodology/approach Three online app-based food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
0
31
1
Order By: Relevance
“…The second set of studies focused on the continuous usage intention of OFD apps during the COVID-19 outbreak period in different countries, such as India ( Mehrolia et al, 2021 ), the USA ( Hong et al, 2021 , Hong et al, 2021 ), China ( Zhao and Bacao, 2020 ), Brazil ( Zanetta et al, 2021 ), Mexico ( Ramos, 2021 ), Vietnam ( Tran, 2021 ). These and several other studies have found that performance expectancy ( Mehrolia et al, 2021 ; Zanetta et al, 2021 ; Pal et al, 2021 ; Ramos, 2021 ), habit ( Zanetta et al, 2021 ; Rydell and Kucera, 2021 ), effort expectancy ( Kumar and Shah, 2021 ; Ramos, 2021 ; Pal et al, 2021 ), price saving orientation ( van Doorn, 2020 ; Ramos, 2021 ; Pal et al, 2021 ), perceived usefulness, and employee trust ( Gavilan et al, 2021 ; Chakraborty et al, 2022 ; Trivedi and Singh, 2021 ; Uzir et al, 2021 ) affect consumers intention to use OFD services during the COVID-19 period.…”
Section: Literature Reviewmentioning
confidence: 59%
See 2 more Smart Citations
“…The second set of studies focused on the continuous usage intention of OFD apps during the COVID-19 outbreak period in different countries, such as India ( Mehrolia et al, 2021 ), the USA ( Hong et al, 2021 , Hong et al, 2021 ), China ( Zhao and Bacao, 2020 ), Brazil ( Zanetta et al, 2021 ), Mexico ( Ramos, 2021 ), Vietnam ( Tran, 2021 ). These and several other studies have found that performance expectancy ( Mehrolia et al, 2021 ; Zanetta et al, 2021 ; Pal et al, 2021 ; Ramos, 2021 ), habit ( Zanetta et al, 2021 ; Rydell and Kucera, 2021 ), effort expectancy ( Kumar and Shah, 2021 ; Ramos, 2021 ; Pal et al, 2021 ), price saving orientation ( van Doorn, 2020 ; Ramos, 2021 ; Pal et al, 2021 ), perceived usefulness, and employee trust ( Gavilan et al, 2021 ; Chakraborty et al, 2022 ; Trivedi and Singh, 2021 ; Uzir et al, 2021 ) affect consumers intention to use OFD services during the COVID-19 period.…”
Section: Literature Reviewmentioning
confidence: 59%
“…Several studies ( Dsouza and Sharma, 2021 ; Mehrolia et al, 2021 ; Pal et al, 2021 ) have been conducted to understand OFD companies and customers' purchase behaviors in the Indian market. Trivedi and Singh (2021) found that Zomato received the most positive and less negative customer sentiments than other competitors, such as Swiggy in India. Dsouza and Sharma (2021) found that the food quality and safety measure of OFDAs positively affects customer satisfaction and loyalty in India.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Over the past couple of decades, there has been a good amount of research published on the application of ML techniques to perform sentiment analysis in the FDS domain [ 13 , 28 , 29 , 30 , 31 ]. Sentiment analysis of customer reviews from tweets for various FDSs, such as Swiggy, Zomato and Uber Eats, was performed to understand consumer satisfaction [ 32 ]. The customer reviews were pulled from Twitter using R-Studio, and the Lexicon-based sentiment analysis method was used on the tweets.…”
Section: Related Workmentioning
confidence: 99%
“…A research paper by Trivedi and Singh (2021) analyzes the social media content of customers, as a way of gathering data with which to understand their sentiment towards a product or service. In this case, data were gathered from the Twitter accounts of the three main online food app delivery services operating in India – namely the food-tech companies UberEats, Zomato, and Swiggy.…”
mentioning
confidence: 99%